RELIGIOUS PLURALISM AND SOCIAL RELATIONS: A SOCIOLOGICAL STUDY OF THE INTERACTION OF HINDUS WITH OTHER COMMUNITIES IN SINGARAJA CITY - Eka Suadnyana, Ida Bagus Putu (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Religious pluralism in Indonesia is not only a sociological reality, but also a challenge in building inclusive and sustainable social relations. This article critically examines the dynamics of religious pluralism in the context of Hindu society in Singaraja City, North Bali, with a focus on the forms of social interaction between Hindus and other religious communities such as Islam, Christianity, and Buddhism. With a sociology of religion approach and the theoretical framework of Durkheim's functionalism, Blumer's symbolic interactionism, and Diana Eck's theological pluralism, this article offers a reflective reading of the practice of interfaith coexistence in urban social and cultural spaces. The results of the study show that Hindu society in Singaraja tends to internalize local wisdom values such as Tat Twam Asi , Tri Hita Karana , and the principle of desa kala patra as an ethical basis for establishing interfaith relations. The social relations formed are functional, both in the form of social cooperation, participation in interfaith activities, and involvement in formal forums such as FKUB. However, the ongoing pluralism still faces a number of challenges, including symbolic segregation, inequality of participation in political and social spaces, and interfaith dialogue that has not yet reached the grassroots level. This article argues that constructive pluralism demands more reflective, participatory, and equal social relations, not only through narratives of tolerance, but through strengthening inclusive social structures and recognizing diversity as social capital. Thus, the context of pluralism in Singaraja is not only relevant as an object of local study, but also as a micro model in understanding the dynamics of social integration and religious identity in Indonesia more broadly.